Experimental security analysis a four-photon private state - Dobek, K; Karpiński, M; Demkowicz-Dobrzański, R; Banaszek, K; Horodecki, P (2011)
We report experimental generation of a noisy entangled four-photon state that exhibits a separation between secure key contents and distillable entanglement. This difference is exposed by a detailed analysis of its privacy properties. © 2010 Optical Society of America.